Das Deutsche als europäische Sprache Ein Porträt - Zifonun, Gisela (De Gruyter, 2021)
As one of the world's 7,000 languages, German shares "family similarities" with many other European languages, but also has some very unique traits. In a total of eight chapters, this book examines the German language within the context of its European neighbour languages and shows where its distinctive features lie, making it clear that facts from its grammar and vocabulary are an interesting and underrated field of knowledge.